2022
DOI: 10.1098/rsif.2022.0072
|View full text |Cite
|
Sign up to set email alerts
|

Fast free-energy-based neutral set size estimates for the RNA genotype–phenotype map

Abstract: The genotype–phenotype (GP) map of RNA secondary structure links each RNA sequence to its corresponding secondary structure. Previous research has shown that the large-scale structural properties of GP maps, such as the size of neutral sets in genotype space, can influence evolutionary outcomes. In order to use neutral set sizes, efficient and accurate computational methods are needed to compute them. Here, we propose a new method, which is based on free energy estimates and is much faster than existing sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
(261 reference statements)
2
9
0
Order By: Relevance
“…3, or not, as shown in section S1 of the SI. This result agrees with existing computational data for the RNAshapes model (SI of ref [6]) and is consistent with our previous work showing correlations between various phenotypic frequency definitions in RNA [22]. It is also consistent with theoretical arguments [23] for a Boltzmann-like trend in phenotypic frequencies, where energetically unfavourable features are associated with an exponential decrease in phenotypic frequencies.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3, or not, as shown in section S1 of the SI. This result agrees with existing computational data for the RNAshapes model (SI of ref [6]) and is consistent with our previous work showing correlations between various phenotypic frequency definitions in RNA [22]. It is also consistent with theoretical arguments [23] for a Boltzmann-like trend in phenotypic frequencies, where energetically unfavourable features are associated with an exponential decrease in phenotypic frequencies.…”
Section: Resultssupporting
confidence: 93%
“…Finally, the fact that the shared number of compatible sequences only gives an upper bound for ϕ qp values is consistent with our previous result for neutral set sizes, where the number of base pairs and hence compatible sequences was found to be only weakly predictive of neutral set size [13]. We found that thermodynamic considerations are also necessary since the fraction of compatible sequences that actually adopt the structure as a mfe structure differs considerably from structure to structure [13].…”
Section: Supplementary Informationsupporting
confidence: 90%
See 1 more Smart Citation
“…This GP map feature was also shown to create a negative correlation between plasticity and robustness [15]. The work from Meyers and Fontana as well as further more recent work [16][17][18][19][20][21] that includes plasticity, has improved our understanding of the plastic GP map but has not fully addressed how concepts such as robustness, evolvability and neutral spaces can be quantified for the non-deterministic case in a way that is consistent with averages over their deterministic counterparts. Thermal fluctuations are ubiquitous in molecular environments, which means that many-to-many GP maps that include plasticity are more biologically realistic in the context of molecular evolution.…”
Section: Introductionmentioning
confidence: 99%
“…7 is based on sampling, as explained in the following and tested in the SM: first a structure sample of 10 4 distinct structures was selected as in ref. [20], by randomly drawing from a list of all valid secondary structures of L = 30. To exclude non-foldable structures, a structure was only included in the sample if a sequence folding into the structure was found after ten iterations of ViennaRNA's inverse folding function.…”
mentioning
confidence: 99%